Assessing electronic device use behaviours in healthy adults: development and evaluation of a novel tool - Naomi K. Fitzpatrick; Veronique Chachay; Sandra Capra; David Briskey; Sarah Jackman; Angela Shore; Joanna Bowtell (BMC, 2024)
Abstract Background Chronic exposure of the macula to blue light from electronic devices has been identified as a potential macular health concern. The impacts remain poorly investigated as no validated methods to capture usual device use behaviours exist. Purpose The aim of this study was to develop and validate the Electronic Device Use Questionnaire (EDUQ) against multiple 24-h electronic device use diaries in healthy Australian and United Kingdom adults. Methods The EDUQ and diaries were developed to capture device use across categories (television, computer and handheld devices). Over eight weeks 56 Australian and 24 United Kingdom participants completed three questionnaires and eight diaries via online platforms. Tool validity was determined through Bland-Altman plot analysis of mean daily hours of device use between the tools. Results The EDUQ demonstrated poor validity in both cohorts with poor agreement when compared with the diaries. When the device categories were combined, a mean difference between the tools of 1.54 h/day, and 95% limits of agreement between -2.72 h/day and 5.80 h/day was observed in the Australian cohort. Across both cohorts and all device categories the mean differences indicated individuals were more likely to report higher device use through the questionnaire rather than diaries. Conclusions The EDUQ is a novel tool and demonstrated the difficulty for participants of accurately recalling usual behaviour of device use. Poor agreement in reported device use occurred across all device categories. The poor agreement may be related to factors such as memory recall bias, and the number of diaries captured not being reflective of usual use. Future studies should look to address these factors to improve validity of device use capture.